Overview of Chilean and Peruvian social policies: Impressions from a study tour - Pedro Lara de Arruda; Luísa A. Nazareno; Manoel Salles; Juliana Alves; Amelie Courau (International Policy Centre for Inclusive Growth (IPC-IG), 2016)
This report follows a study tour undertaken on 5-16 October 2014 by a team of experts from the Planning Institute of Jamaica (PIOJ), who sought to gain practical knowledge on the operational and institutional aspects of Chilean and Peruvian social programmes and policies. The study tour took place due to collaboration with the UNDP Country Offices and the stakeholders involved in social policies in these countries. It also received support from the IPC-IG in terms of both organising the agenda for the visits and providing the PIOJ team with a researcher/specialist to provide additional analytical inputs to contextualise and make critical sense of the policies and programmes observed. [...]
Keywords: 330; overview; Chile; Peru; social policies; impressions; study tour